2006
DOI: 10.1292/jvms.68.589
|View full text |Cite
|
Sign up to set email alerts
|

The Histopathogenesis of Paralytic Rabies in Six-Week-Old C57BL/6J Mice Following Inoculation of the CVS-11 Strain into the Right Triceps Surae Muscle

Abstract: ABSTRACT. A fatal encephalomyelitis was developed after intracerebral and hind limb inoculation of in 6-week-old C57BL/6J mice by the inoculation of fixed rabies virus (CVS-11 strain), intracerebrally and into hind. After the intracerebral inoculation, virus antigens were detected in the cerebral cortex and hippocampus at 2 days postinoculation (PI), and later spread centrifugally to thalamus, brain stem, cerebellum, spinal cord and spinal ganglia. At 4 days PI, severe apoptosis and DNA fragmentation were obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…Previous histopathological studies showed that RABV replicates in muscle cells before infecting peripheral nerves, implying that viral replication in muscle cells enhances the infection of peripheral nerves (7)(8)(9)(10). However, this possibility has not been supported by experimental data showing a correlation between the abilities of the virus to replicate in muscle cells and to infect peripheral nerves.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous histopathological studies showed that RABV replicates in muscle cells before infecting peripheral nerves, implying that viral replication in muscle cells enhances the infection of peripheral nerves (7)(8)(9)(10). However, this possibility has not been supported by experimental data showing a correlation between the abilities of the virus to replicate in muscle cells and to infect peripheral nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using both street and fixed RABV strains have demonstrated that muscle cells are the infection sites in peripheral tissue (7)(8)(9)(10)45). In this study, we compared in vivo replication efficiencies of the Ni-Luc, Ni-CE-Luc, and CE(NiP)-Luc strains in muscle and obtained data strongly suggesting that the Ni P gene, but not the Ni-CE P gene, mediates stable viral replication in muscle (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The spinal lesions were composed of the infiltration of T lymphocytes, the increase of microglial cells and astroglial cells and the majority of T lymphocytes exhibited apoptosis. In contrast, marked neuronal apoptosis was detected in the cerebral cortex, hippocampus and cerebellum of mice that were inoculated intracerebrally with CVS-11, but paralysis was absent [21]. Induction of apoptosis by fixed strain of rabies virus has been reported in vitro [19] and experimental animal models [11,13] to be associated with the expression level of the virus protein.…”
mentioning
confidence: 99%